Enantioselective addition of diethylzinc to aldehydes catalyzed by 5-cis-substituted proline derivatives. Issue 1 (3rd January 2019) - Prause, Felix; Wagner, Stefan; Breuning, Matthias
Abstract: 5- Cis -substituted prolinols, prolinamines, and prolinamine sulfonamides proved to be efficient ligands for the enantioselective addition of diethylzinc to aldehydes, providing up to 99% ee. The sense of asymmetric induction can be controlled by the nature of the exocyclic functional group (CPh2 OH vs. CH2 NHR vs. CH2 NHSO3 R). The additional 5- cis substituent exerts a strong beneficial effect on the chirality transfer since it rigidifies the catalyst structure. The stereochemical outcome of the reactions is discussed in detail on the respective transition states. Graphical abstract: